Electronic value exchange origins of the VISA electronic payment system - Stearns, David L.; SpringerLink (Online service). (London Springer, 2011)
Although those born after the 1990s might never have known a time without them, payment cards and the electronic and computing networks they activate went through an explicit process of creation and adoption a process which actively shaped these ubiquitous systems into what they are today. To understand why these systems ended up the way they did, one first needs to understand their origins, and how decisions made in their early years fundamentally shaped the way they evolved. Electronic Value Exchange recaptures the origins of one of these systems in particular: the electronic payment network known as VISA. The book examines in detail the transformation of the VISA system from a collection of non-integrated, localized, paper-based bank credit card programs into the cooperative, global, electronic value exchange network it is today. Following an introductory chapter that sets the context, chapters adhere roughly to chronological order, building the story in a logical fashion. Topics and features: Provides a history of the VISA system from the mid-1960s to the early 1980s, charting the design, creation and adoption of the system during its foundation years and most prolific period of innovation Presents a historical narrative based on research gathered from personal documents and interviews with key actors who designed, built, and participated in the VISA payment system Investigates, for the first time, both the technological and social infrastructures necessary for the VISA system to operate Supplies a detailed case study, highlighting the mutual shaping of technology and social relations, and the influence that earlier information processing practices have on the way firms adopt computers and telecommunications Examines how gateways in transactional networks can reinforce or undermine established social boundaries, and reviews the establishment of trust in new payment devices This insightful work will be of interest to researchers from a range of disciplines, from historians of technology, business and finance, to economists and sociologists, as well as the general reader. The use of academic jargon is kept to a minimum, and brief explanations are provided of useful concepts from science and technology studies for the benefit of those without a background in this field. Dr. David L. Stearns is an adjunct lecturer in history at Seattle Pacific University, Seattle, USA. Prior to his return to academia, he was a software developer and designer for nearly twenty years.
Setting the Stage: Money, Credit, and Payments in America - Associating: Dee Hock and the Creation of the Organization - Crafting the Social Dynamics: Staffing, Operating Regulations, and Advertising - Automating Authorization: BASE - Automating Clearing and Settlement: BASE II and III - Expanding the System: Organizational and Technical Growth - Automating the Point of Sale: Encoding Standards and Merchant Dial Terminals - Challenging Conceptual Barriers: EFT and The Debit Card - Negotiating Roles: Controversies and the End of an Era - Conclusions: Towards a General Socio-technical History of Payment Systems.
Electronic reproduction.
Keywords: VISA International; Electronic funds transfers -- History; Electronic books